PENGARUH KEPEMIMPINAN STRUKTUR INISIASI, KINERJA NON FINANSIAL DAN LEVERS OF CONTROL TERHADAP KEJELASAN TUJUAN - Rika Neldawaty; Riski Hernando (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
The purpose of this study was to examine the direct influence of leaders who use the initiation structure leadership style on the goal clarity. This study also examined the indirect effect of the relationship between the leadership style of the initiation structure on the goal clarity that was mediated by subjective diagnostics and subjective interactive. This study was tested using a sample of 152 employees who work at manufacturing, service and trading companies located in the Jabodetabek area. The research data were obtained from questionnaires distributed to respondents and analyzed using structural equation modeling - partial least square (SEM-PLS) with WarpPLS 3.0 software. The results of this study found that the direct effect of the initiation structure leadership style has a significant positive effect on the clarity of objectives. On the other hand, the indirect influence by subjective diagnostic and subjective interactive is able to partially mediate the relationship between the leadership style of the initiation structure on the goal clarity.